Non-sponsored brand-related user-generated content: Effects and mechanisms of consumer engagement - Davcik, N.; Langaro, D.; Jevons, C.; Nascimento, R. (Journal of Product and Brand Management, 2022)
Purpose – The current study investigates whether users’ engagement with the social media platform is affected as they engage in non-sponsored brand-related user-generated content (UGC). The concept of non-sponsored brand-related UGC encapsulates various social media patterns in which individuals choose how to consume, contribute or create brand related content with no formal brand incentive or control. Design/methodology/approach – The study focuses on the question of how users engage with non-sponsored brand-related UGC on Instagram and assesses the influence of UGC perceived value. The variance-based structural equation modeling (SEM) approach using partial least squares (PLS) was applied. Findings – The research shows significant and positive effects of UGC on Instagram users´ intentions to engage with the platform and the influence of UGC perceived value on UGC uses. The findings deepen our understanding of the mechanisms underlying non-sponsored brand-related UGC in consumer engagement marketing, with significant implications for brand managers and the future development of Instagram and other social media platforms. Originality – The UGC functional, social and emotional values are evaluated for their effects on generating the three distinct patterns of consumer online brand related activities (consumer, contribute and create) in the non-sponsored brand-related UGC context.